(untitled) (Defense and Security Studies, 2023)
As a developing country, Indonesia must effectively manage its national defense by implementing defense policies which can be interpreted as management activities that transform into defense policy management entities. The objective is to protect against various dangerous threats resulting from the dynamics of the current strategic environment, which continues to undergo rapid and significant changes. Cyber threats pose a potentially dangerous threat that has a multidimensional impact. Therefore, this article analyzes one of the Indonesian government’s efforts to deal with cyber threats, which is in the form of Presidential Regulation No. 47 of 2023. The research employs a qualitative descriptive approach in the field of literacy studies, drawing on reputable sources such as journals, books, and internet materials. It investigates the management measures and strategies implemented by Indonesia to combat cyber threats in accordance with presidential regulations for cybersecurity. These findings elaborate on the implementation of presidential regulations that concentrate on cyber crisis management and national cyber security strategy as a suitable and praiseworthy response to the constantly evolving cyber threats. Nonetheless, addressing several challenges requires strategic competencies in leadership to formulate cyber defense policies and strategies and carry them out optimally.